1991
DOI: 10.1083/jcb.115.4.1171
|View full text |Cite
|
Sign up to set email alerts
|

Elevated extracellular calcium concentrations induce type X collagen synthesis in chondrocyte cultures.

Abstract: Abstract. Chondrocytes at different stages of cellular differentiation were isolated from the tarsal element (immature chondrocytes) and zones 2 and 3 (mature chondrocytes) of 12-d chick embryo tibiotarsus. The chondrocytes from the two sources differed in their cell morphologies, growth rate and production of type X collagen . In 24 h, zone 2 and 3 chondrocytes synthesized 800 times more type X collagen than tarsal chondrocytes . The effect of exogenous CaC12 (5 and 10 mM) on the synthesis of type X collagen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(50 citation statements)
references
References 58 publications
(52 reference statements)
1
49
0
Order By: Relevance
“…Collagen production was reported to be the lowest at [Ca 2+ ] = 1 to 2mM in a chondrocyte-monolayer study, and an increase of [Ca 2+ ] from 2mM stimulated collagen production [12]. Other studies show that a lower calcium level can stimulate the Type X collagen synthesis and suppress the Type I collagen synthesis while leaving the Type II collagen unchanged [46,47]. No significant effect of calcium concentration on GAG production has been reported.…”
Section: Discussionmentioning
confidence: 96%
“…Collagen production was reported to be the lowest at [Ca 2+ ] = 1 to 2mM in a chondrocyte-monolayer study, and an increase of [Ca 2+ ] from 2mM stimulated collagen production [12]. Other studies show that a lower calcium level can stimulate the Type X collagen synthesis and suppress the Type I collagen synthesis while leaving the Type II collagen unchanged [46,47]. No significant effect of calcium concentration on GAG production has been reported.…”
Section: Discussionmentioning
confidence: 96%
“…Of particular interest here is the work of Deshmukh and colleagues (Deshmukh et al, 1976, which demonstrates that isolated chondrocytes, when maintained in suspension culture, produce primarily type I1 collagen in medium lacking CaCl,, and type I collagen in complete medium. Mature chondrocytes isolated from sternal hyaline cartilage also express type X collagen when cultured in excess medium calcium (Bonen and Schmid, 1991). Additionally, several studies concluded that a critical concentration of intracellular calcium is necessary for normal synthesis of skeletal extracellular matrix and Chojkier, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Whether this inhibition occurs at the level of transcription, translation, or secretion is under investigation. In the presence of elevated concentrations of extracellular calcium, type X collagen synthesis is increased dramatically while type I1 collagen synthesis is not increased (39). Chondrocytes are sensitive to changes in intracellular calcium concentrations, beginning with their initial differentiation from mesenchyma (40).…”
Section: Discussionmentioning
confidence: 99%